Prevalence and age-related trends of refractive errors in Mexican outpatients: a cross-sectional study - García-Gil, Abraham; Hernández-Jurado, Beatriz Itzel; Luna-Ruiz-Esparza, Marco Antonio; Espinoza-Angulo, Eduardo; Machado-Jiménez, Héctor; Gómez-Campaña, Humberto; Campos-Romero, Abraham; Alcántar-Fernández, Jonathan (Frontiers in Public Health, 2025)
BackgroundRefractive errors (RE) are the leading cause of visual impairment and blindness worldwide. With ongoing demographic shifts, including population growth, aging, and lifestyle changes, the global prevalence of RE is expected to rise. Robust epidemiological data are essential to mitigate their public health impact. However, in Mexico, comprehensive studies assessing the burden of RE across age groups and regions are scarce.ObjectiveThis study aimed to characterize the epidemiological profile of RE in Mexico using a large outpatient sample, focusing on geographic distribution and variation by sex and age.MethodsWe analyzed an electronic database of eye examinations from 3.8 million outpatients who attended Salud Digna clinics across Mexico in 2024. Prevalence estimates were calculated with 95% confidence intervals (CIs), and statistical comparisons were performed to assess differences by sex and age.ResultsThe overall prevalence of RE was 74.61% (95% CI, 74.57–74.65) with 2,841,067 outpatients affected. Myopia was the most common condition, affecting 1,469,377 outpatients (38.6, 95% CI, 38.54–38.64), followed by hyperopia (1,234,403 affected outpatients, 32.4, 95% CI, 32.37–32.47) and astigmatism (1,205,400 affected outpatients, 31.7, 95% CI, 31.61–31.71). Astigmatism was significantly more prevalent in males across all age groups (p < 0.001). Myopia and hyperopia showed similar prevalence between sexes during childhood and early adulthood, but diverged in later adulthood, with higher rates of myopia in males (p < 0.001) and hyperopia in females (p < 0.001). All three RE types exhibited a marked shift in prevalence in the 40–49 age group. Geographic variation was observed, with central states showing higher astigmatism and myopia prevalences rates whereas coastal states showed higher hyperopia prevalence rates. Notably, a large proportion of outpatients have never undergone an eye examination, indicating substantial gaps in access to care.ConclusionThis outpatient-based study provides critical insights into the epidemiology of RE in Mexico, revealing significant demographic and geographic disparities. The findings underscore the urgent need for targeted public health strategies to improve access to eye care services, particularly for underserved populations and high-risk age groups.